2021
DOI: 10.2196/26703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Personalized Smartphone App on Bowel Preparation Quality: Randomized Controlled Trial

Abstract: Background Adequate bowel preparation is essential for the visualization of the colonic mucosa during colonoscopy. However, the rate of inadequate bowel preparation is still high, ranging from 18% to 35%; this may lead to a higher risk of missing clinically relevant lesions, procedural difficulties, prolonged procedural time, an increased number of interval colorectal carcinomas, and additional health care costs. Objective The aims of this study are to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…With the development of science and technology, social media apps and public websites have also become a way to educate patients about bowel preparation. zander Team independently developed a smartphone application, patients can run the application on android or ios equipment, the application provides information and conventional hospital education content is very similar, but the way of information is more intuitive, namely according to the patient appointment colonoscopy time customization, provide patients need to achieve intestinal cleaning degree of low residue food image, laxative intake method and image, provide personalized intestinal preparation steps, the results showed that the quality of gut preparation was significantly better in the smartphone app population compared to the control group [5]. Guan Y Team uses WeChat, a smart Chinese instant messaging and social media application, let colonoscopy or their families in booking time scan or codes WeChat group, the medical staff WeChat group with text, pictures, videos telling the importance of intestinal preparation, dietary requirements, and diarrhea drug medication instructions, etc., the results show that using WeChat group, can improve the quality of intestinal preparation and increase the adenoma detection rate, shorten the total time of colonoscopy, and reduce the discomfort in intestinal preparation [6].…”
Section: Preoperative Education and Bowel Preparationmentioning
confidence: 99%
“…With the development of science and technology, social media apps and public websites have also become a way to educate patients about bowel preparation. zander Team independently developed a smartphone application, patients can run the application on android or ios equipment, the application provides information and conventional hospital education content is very similar, but the way of information is more intuitive, namely according to the patient appointment colonoscopy time customization, provide patients need to achieve intestinal cleaning degree of low residue food image, laxative intake method and image, provide personalized intestinal preparation steps, the results showed that the quality of gut preparation was significantly better in the smartphone app population compared to the control group [5]. Guan Y Team uses WeChat, a smart Chinese instant messaging and social media application, let colonoscopy or their families in booking time scan or codes WeChat group, the medical staff WeChat group with text, pictures, videos telling the importance of intestinal preparation, dietary requirements, and diarrhea drug medication instructions, etc., the results show that using WeChat group, can improve the quality of intestinal preparation and increase the adenoma detection rate, shorten the total time of colonoscopy, and reduce the discomfort in intestinal preparation [6].…”
Section: Preoperative Education and Bowel Preparationmentioning
confidence: 99%
“…Further research has been conducted by scholars in this field. van der Zander [9] and others developed a smartphone application called Prepit (Ferring B V), which consists of six parts: colonoscopy examination date, educational tools, bowel preparation schedule, low-fiber diet examples, visually assisted preparation instructions, and examples of transparent liquid intake. They provided oral and written education to 86 patients while the remaining 87 patients followed the steps outlined in the smartphone application for bowel cleansing preparation.…”
Section: Research Progress Of Ai In Bowel Preparationmentioning
confidence: 99%
“…Chief among these advantages is that pictograms can be more easily understood than their written counterparts [ 8 , 9 , 18 , 20 , 26 , 28 , 30 , 31 ]. When it comes to health care, pictograms have been shown to be better at informing patients about examination preparation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%